Estimating of Hoek-Brown mi Using Internal Friction Angle - Mehrishal, S.; Sharifzadeh, Mostafa; Shahryar, K. (TMMOB Maden Muhendisleri Odasi, 2015)
Application of Hoek-Brown failure criterion in rock mechanics is more common and is verified well. In this criterion, the mi is an important factor which controls trend of failure curve. Based on rock type and triaxial test data, the method of mi estimation for different rocks is provided by Hoek-Brown. Indeed, this parameter is a frictional property and it depends on rock type, mineralogy and granular interlocking of rocks. In addition, it can be approximately predicted from the ratio between the uniaxial compressive strength and tensile strength of brittle intact rocks. But, because of tension strength estimation difficulties, this method is not applicable well. In this paper, correlation of mi and internal friction angle (f) of intact rocks is investigated and based on this correlation; a comprehensible physical concept is introduced for this parameter. Therefore, using this concept, a simple and exact estimation method is developed for mi and H-B failure criterion calculation. The results predicted by new method are well verified by comparison with experimental test results.